Kajian Risiko Pajanan Dermal Insektisida pada aktivitas Cold Fogging kepada Teknisi Pengendali Hama PT. X Jakarta - Lutfi Muzaqi; Mila Tejamaya (Pro Health Jurnal Ilmiah Kesehatan, 2019)
Insecticides are one type of pesticide that is widely used in the community to protect public health. History has proven that the development of pesticides and insecticides has succeeded in reducing the rate of malaria, filariasis, onchocerciasis, and other infectious diseases. However, toxicity of pesticide may expose to pest control officer as well. During the process of manufacturing, mixing and applying insecticides, workers are exposed to chemical hazards from thr active ingredient of pesticide and risk to their health. In this study, insecticide dermal exposure to the pest controll technicians during cold fogging job was assessed using the semi-quantitative method, called DREAM (Dermal Risk Exposure Method). The unit of analysis consisted of pouring the insecticides from a concentrated bottle into a measuring cup, mixing insecticides with water, pouring the insecticide mixture into the fogging machine, and perform cold fogging. The amount of total dermal exposure was influenced by adsorption from emissions, desposition and transfer, and type of active ingredient, hand protection, and length of exposure. It was found that total dermal exposure during the activity of pouring insecticides from the concentrate bottle into a measuring cup was 11.90 (very low dermal exposure), during mixing waterbased insecticides was 11.90 (very low dermal exposure), pouring insecticide into the machine was 29.40 ( low dermal exposure) and cold fogging activities was 33.61 (moderate dermal exposure). Total actual dermal exposure were combination of those activities and gave value 86,83 that fell into moderate risk category.